Rhinogenic optic neuropathy with hemianopia caused by ethmoidal sinus mucocele. Issue 12 (5th December 2022) - Oka, Kosuke; Ando, Wataru; Hagiya, Hideharu; Higaki, Takaya; Otsuka, Fumio
Abstract: A patient complained of acute right vision loss and headache. A computed tomography scan revealed ethmoidal sinus mucocele in the right ethmoid sinus that was compressing the optic nerve and emergency endoscopic sinus surgery was performed. Abstract : A patient complained of acute right vision loss and headache. A computed tomography scan revealed ethmoidal sinus mucocele in the right ethmoid sinus that was compressing the optic nerve and emergency endoscopic sinus surgery was performed.